2019
DOI: 10.1071/rd18136
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-mediated DNA lesions alter metabolite levels in spent embryo culture medium

Abstract: Paternal genetic alterations may affect embryo viability and reproductive outcomes. Currently it is unknown whether embryo metabolism is affected by sperm-mediated abnormalities. Hence, using a mouse model, this study investigated the response to paternally transmitted DNA lesions on genetic integrity and metabolism in preimplantation embryos. Spent embryo culture media were analysed for metabolites by nuclear magnetic resonance spectroscopy and embryonic genetic integrity was determined by terminal deoxynucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…D'Souza et al [93] used mouse embryo SCM to predict the implantation ability of the embryos which showed the increased requirement of pyruvate and lactate accompanied by a significant reduction of pyruvate/alanine ratio in the SCM. Further, sperm-induced genetic lesions in the embryos are associated with a significant increase in the uptake of pyruvate and reduced pyruvate/alanine ratio in SCM [113]. Data from animal studies provide only fundamental knowledge but cannot be directly extrapolated to human ART due to species-specific differences in the metabolic requirements, chromatin architecture and developmental timelines.…”
Section: Composition Of the Different Embryo Culture Mediamentioning
confidence: 99%
“…D'Souza et al [93] used mouse embryo SCM to predict the implantation ability of the embryos which showed the increased requirement of pyruvate and lactate accompanied by a significant reduction of pyruvate/alanine ratio in the SCM. Further, sperm-induced genetic lesions in the embryos are associated with a significant increase in the uptake of pyruvate and reduced pyruvate/alanine ratio in SCM [113]. Data from animal studies provide only fundamental knowledge but cannot be directly extrapolated to human ART due to species-specific differences in the metabolic requirements, chromatin architecture and developmental timelines.…”
Section: Composition Of the Different Embryo Culture Mediamentioning
confidence: 99%
“…Paternal genetic alterations may affect embryo viability and reproductive outcomes. It has been shown that paternally transmitted DNA lesions influence the metabolism in preimplantation embryos [31,56]. Low glutamine level was found on day 3 SCM in male factor patients [31].…”
Section: Fig 2)mentioning
confidence: 99%
“…Since ICSI completely bypasses natural sperm selection, we investigated the differences in the level of metabolites in relation to sperm DNA fragmentation and sperm head defects. Embryos derived from DNA fragmented spermatozoa progressed normally until the blastocyst stage, showed reduced pyruvate-to-alanine ratio in SCM [56]. Hence, we tested the spent medium from the optimal quality blastocyst on day 5.…”
Section: Fig 2)mentioning
confidence: 99%
“…Therefore, most of the studies in the literature have correlated the embryonic response to the sperm OS with reference to the sperm DNA damage. The response to the entry of spermatozoa carrying DNA damage to the ooplasm during fertilization can have various consequences [81,82,[186][187][188][189]. Depending on the extent of sperm DNA damage, the oocyte can repair the damage in spermatozoa and lead to a healthy embryo; it can successfully fertilize with the development of the defective embryo, or it may lead to fertilization failure or embryo arrest [190].…”
Section: Effects Of Sperm Os On Embryo Developmentmentioning
confidence: 99%